Development of disulfide-functionalized peptides covalently binding G protein-coupled receptors - Einsiedel, Jürgen; Schmidt, Maximilian; Hübner, Harald; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2022)
A broadly applicable synthesis of peptides incorporating mixed disulfides between cysteine and homocysteine and cysteamine was developed. The method was established using pharmacologically relevant G protein-coupled receptor (GPCR) ligands including the μ-receptor agonist Dmt-DALDA and extended to the orexin derivative Oxa(17–33) and NT(8–13), the C-terminal hexapeptide of neurotensin. The newly developed NT(8–13) analog 6b incorporating an S-functionalized homocysteine revealed covalent binding of the neurotensin receptor 1 (NTSR1) in a radioligand depletion study.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Covalent ligand; Disulfide tethering; G protein-coupled receptor; Neurotensin receptor